Impact of socioeconomic status on participation and outcomes in the Salford Lung Studies. Issue 1 (16th March 2020) - Jones, Rupert; Nicholls, Andy; Browning, Dominy; Diar Bakerly, Nawar; Woodcock, Ashley; Vestbo, Jørgen; Leather, David A.; Jacques, Loretta; Lay-Flurrie, James; Svedsater, Henrik; Collier, Susan
COPD and asthma prevalence is associated with socioeconomic status (or "deprivation"), yet deprivation is rarely considered in typical large-scale efficacy randomised controlled trials that recruit highly selected patient populations. In this post hoc analysis of the Salford Lung Studies in COPD and asthma (two 12-month, open-label, effectiveness randomised controlled trials conducted in UK primary care), we evaluated the impact of patient deprivation on clinical outcomes with initiating fluticasone furoate/vilanterol versus continuing usual care. Patients were categorised into deprivation quintiles based on postcode and a countrywide database of indices of deprivation, and trial outcomes by quintile were assessed. 52% of patients in the COPD study were included in the most deprived quintile, contrasting with 20% in the asthma study. Greater deprivation was associated with higher rates of primary/secondary healthcare contacts and costs. However, the treatment effect of fluticasone furoate/vilanterol versus usual care for primary (COPD: moderate/severe exacerbations; asthma: Asthma Control Test responders at week 24) and secondary/other (healthcare consumption, adherence, treatment modifications, study withdrawals, exacerbations, serious adverse events) outcomes was similar across deprivation quintiles. Our findings support the recruitment of participants from all socioeconomic strata to allow assessment of data generalisability to routine clinical practice. Deprivation did not impact the main outcomes of the SLS, thus supporting recruitment of participants from all socioeconomic strata to randomised controlled trials for assessment of generalisability of study findings to routine clinical practice http://bit.ly/34qk9EH